The content of reablement: Exploring occupational and physiotherapy interventions. (February 2019) - Zingmark, Magnus; Evertsson, Bodil; Haak, Maria
Statement of context: Occupational therapists and physiotherapists in a Swedish municipality answered a web-based survey about their reablement interventions. Critical reflection on practice: There were overlapping areas as well as differences regarding the focus of occupational and physiotherapy interventions. Regarding the duration of interventions, occupational therapy was implemented over a short time span in contrast to physiotherapy, which had a longer duration. Both professions used valid and reliable instruments to a very limited extent. Implications for practice: If other areas than self-care and mobility are to be addressed within reablement there is a need to critically reflect on the focus, content and duration of reablement interventions. Valid and reliable assessments can be utilised to a greater extent to guide goal-setting, the focus of interventions and to evaluate effects.